Enhancing Student Outcomes in Acid-Base Titration Through Assessment for Learning - Ningtryas, Klara Dinda Ayu; Muchlis, Muchlis; Harahap, Ilham Pradana Putra (Jurnal Pijar Mipa, 2025)
The purpose of this study was to describe the implementation of assessment for learning-oriented learning and learning outcomes on acid-base titration material in class XI. This research was conducted in class XI-1 and XI-5 SMA Giki 1 Surabaya. The results showed that the implementation of assessment for learning-oriented learning on acid-base titration material as a whole received very good criteria. This is evidenced by the average percentage of implementation scores at the first meeting of 99.3% and 98.5% for classes XI-1 and XI-5, as well as the second meeting of 99% and 99.5% in classes XI-1 and XI-5 with the criteria for each meeting is very good. Learning outcomes through assessment applications for learning-oriented learning have increased in one sample t-test. The test found that posttest2 XI-5 - posttest2 XI-1 in both classes got a p-score> 0.05, then Ho was accepted, and Ha was rejected. Thus, the score for posttest 2 XI-1 was smaller than that of posttest 2 XI-5. There is no significant difference in posttest 2 between the two classes. So from this, it can be concluded that learning that applies the Assessment for Learning-oriented student worksheet is effective even though the average results of the two classes show differences.